Conditional Use of a Request for Assistance: Considering Generalization. (June 2018) - Reichle, Joe; Byiers, Breanne J.; Reeve, Amanda
Individuals with autism spectrum disorder (ASD) frequently exhibit generalization errors, but many instructional programs fail to address this deficit. Generalization errors encompass when the learner should extend the use of a newly taught behavior to other contexts but does not (under-generalization), as well as when he or she should not use the newly established behavior in new contexts but does (over-generalization). This study was designed to evaluate the generalization errors of a preschooler with ASD. Following an intervention in which the participant was taught to request assistance with difficult tasks using a continuous reinforcement schedule, generalization gradients across levels of task difficulty were implemented to examine patterns of generalization. Initial results showed over-generalization of assistance requests and corresponding reductions in independent (the absence of any instructional prompts) task completion across all levels of task difficulty. A final phase involving competing schedules of reinforcement for assistance requests and independent work with video modeling led to improved conditional use of assistance requests. Implications for teaching conditional use of assistance requests are discussed.